1989
DOI: 10.1677/joe.0.1220323
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of testosterone secretion by the rat testis: implications for measurement of the intratesticular levels of testosterone

Abstract: Testosterone concentrations have been measured in testicular interstitial fluid (IF), and in blood plasma sampled from various parts of the rat testis and spermatic cord, to assess (1) the most accurate method for determination of the intratesticular levels of testosterone, and (2) the route of secretion of testosterone from the testis. In untreated adult rats, testosterone concentrations were highest in blood collected from veins on the surface of the testis (269.50 +/- 30.63 (S.E.M.) nmol/l), but were reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…However, it is the intratesticular level of testosterone which is important for fertility and this cannot be deduced in any precise way from the levels in peripheral blood. This has been demonstrated clearly from our recent studies in the rat (Maddocks & Sharpe, 1989) (see Fig. 1) and has been confirmed in normal men, from whom testicular, spermatic and peripheral venous blood were collected at the time of vasectomy reversal .…”
Section: E F I C I E N C I E S I N I N T R a T E S T I C U L A R C supporting
confidence: 77%
See 1 more Smart Citation
“…However, it is the intratesticular level of testosterone which is important for fertility and this cannot be deduced in any precise way from the levels in peripheral blood. This has been demonstrated clearly from our recent studies in the rat (Maddocks & Sharpe, 1989) (see Fig. 1) and has been confirmed in normal men, from whom testicular, spermatic and peripheral venous blood were collected at the time of vasectomy reversal .…”
Section: E F I C I E N C I E S I N I N T R a T E S T I C U L A R C supporting
confidence: 77%
“…required for spermatogenesis is controlled by the vasculature, as all such compounds must first pass across the vascular endothelium into testicular interstitial fluid (IF) before gaining access to the seminiferous tubules. It has now been shown that IF formation is androgen-regulated, presumably via effects of testosterone on the Sertoli or peritubular cells which then modulate the vasculature by secreting one or more vasoactive factors (Maddocks & Sharpe, 1989). More recently it has been shown that this effect of testosterone involves modulation of testicular blood flow (J. E. Damber, A. Widmark and S. Maddocks, unpublished data).…”
Section: T H E I N T R a T E S T I C U L A R Role(s) O F T E S T O S mentioning
confidence: 98%
“…Furthermore, this concentration of FSH is close to that used by Henriksen et al (1996) (2 ng/ml of FSH from another source), giving a near maximal effect in experiments of incubation of seminiferous tubular segments. As for testosterone, a 'physiologic' concentration (Maddocks & Sharpe 1989) was chosen.…”
Section: Discussionmentioning
confidence: 99%
“…Testicular vein (TV) blood was also collected from the animals in experiment 2, which had been treated for 19 weeks, to determine intratesticular testosterone concentrations (Maddocks & Sharpe 1989). Rats were anaesthetised with halothane and heparinised by injection of 125 IU heparin (Leo Laboratories Ltd, Princes Risborough, Bucks, UK) into the left femoral vein.…”
Section: Collection Of Blood Samples and Testicular Interstitial Fluidmentioning
confidence: 99%
“…Rats were anaesthetised with halothane and heparinised by injection of 125 IU heparin (Leo Laboratories Ltd, Princes Risborough, Bucks, UK) into the left femoral vein. The right testis was exposed via a scrotal incision and TV blood collected into haematocrit tubes by puncturing the major surface testicular vein with a 28-gauge needle at a point just before its division into the mediastinal venous plexus at the anterior pole of the rete (Maddocks & Sharpe 1989).…”
Section: Collection Of Blood Samples and Testicular Interstitial Fluidmentioning
confidence: 99%